PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF CHILD'S PERSONALITY DEVELOPMENT IN MARTIAL LAW CONDITIONS - Beznosyuk , Alexander; Baіrak , Iryna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article deals with the problems of psychological and pedagogical support of a child during the formation of his/her personality in wartime and suggests ways to overcome them.